Pengaruh Green Brand Image terhadap Green Brand Equity melalui Green Brand Trust pada Perusahaan Kecantikan dan Perawatan Tubuh The Body Shop Indonesia - Nathasia Marshellina Suyanto; Sigit Pramono (Holistic Journal of Management Research, 2020)
This study aims to determine the influence of green brand image on green brand equity which is mediated by green brand trust in cosmetics and body care company The Body Shop Indonesia. The research type is explanatory research that explains or proves the relationship or influence the variabel thorugh hypothesis test. Sampling uses a non-probability sampling method with a 170 respondents who had made trancactions or purchased in The Body Shop Indonesia. Data analysis using Structural Equation Modeling (SEM) with SmartPLS 3.0 software (Partial Least Square). The results of this study indicate that (1) green brand image variable has a positive and significant effect on green brand equity in The Body Shop Indonesia company, (2) green brand image variable has a positive and significant effect on green brand trust in The Body Shop Indonesia company, (3) green brand trust variable has a positive and significant effect on green brand equity in The Body Shop Indonesia company, (4) green brand image variable has a positive and significant effect on green brand equity in The Body Shop Indonesia company mediated by green brand trust. The conclusion of this research is that with the presence of green brand trust as a mediating variable, it will be able to build a better relationship between green brand image and green brand equity in the cosmetics and body care company The Body Shop Indonesia. Keywords: Green Brand Image, Green Brand Trust, Green Brand Equity